2006
DOI: 10.1161/circulationaha.105.608828
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Brain Natriuretic Peptide in Preload-Dependent Regulation of Cardiac Sarcoplasmic Reticulum Ca 2+ ATPase Expression

Abstract: Background— In heart failure (HF), ventricular myocardium expresses brain natriuretic peptide (BNP). Despite the association of elevated serum levels with poor prognosis, BNP release is considered beneficial because of its antihypertrophic, vasodilating, and diuretic properties. However, there is evidence that BNP-mediated signaling may adversely influence cardiac remodeling, with further impairment of calcium homeostasis. Methods and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
43
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 42 publications
(44 reference statements)
11
43
1
1
Order By: Relevance
“…Furthermore, mRNA expressions of α-myosin heavy chain (α-MHC; also known as MYH6) and sarcoplasmic reticulum Ca 2+ ATPase (SERCA2a; also known as ATP2A2) were downregulated ( Figure 1, D and E), both of which are characteristic hallmarks of human heart failure (3)(4)(5). In agreement with a previous study (5), an inverse correlation was observed between BNP and SERCA2a expression ( Figure 1F). …”
Section: Characteristic Alterations Of Gene Expression In Human Failisupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, mRNA expressions of α-myosin heavy chain (α-MHC; also known as MYH6) and sarcoplasmic reticulum Ca 2+ ATPase (SERCA2a; also known as ATP2A2) were downregulated ( Figure 1, D and E), both of which are characteristic hallmarks of human heart failure (3)(4)(5). In agreement with a previous study (5), an inverse correlation was observed between BNP and SERCA2a expression ( Figure 1F). …”
Section: Characteristic Alterations Of Gene Expression In Human Failisupporting
confidence: 90%
“…Since no differences between ICM and DCM were detected in most subsequent analyses, unless indicated otherwise, these groups were merged into a single group referred to herein as failing myocardium. As described previously (3)(4)(5), ANP and BNP were upregulated in failing versus nonfailing myocardium, with a close correlation between both natriuretic peptides ( Figure 1, A-C). Furthermore, mRNA expressions of α-myosin heavy chain (α-MHC; also known as MYH6) and sarcoplasmic reticulum Ca 2+ ATPase (SERCA2a; also known as ATP2A2) were downregulated ( Figure 1, D and E), both of which are characteristic hallmarks of human heart failure (3)(4)(5).…”
Section: Characteristic Alterations Of Gene Expression In Human Failisupporting
confidence: 82%
See 1 more Smart Citation
“…Induced downregulation of SERCA in transgenic mice led to an induction of ER stress [24]. We have previously shown that afterload-induced upregulation of BNP counteracts the preload-induced and calcineurin-mediated increase in the expression of SERCA2a [25][26][27]. This upregulation of SERCA2a by preload in the isotonic stretched muscles strips after 6 h might help to keep the intraluminal ER Ca 2+ concentration normal and might therefore protect the cells from ER stress.…”
Section: +mentioning
confidence: 95%
“…Because brain natriuretic peptide has also been found to be significantly upregulated in tni-203/mhc-403 mice and because it has been shown to downregulate serca2a expression, brain natriuretic peptide induction might be, at least in part, responsible for serca2a downregulation. 11 Brain natriuretic peptide gene expression itself depends on activity of the transcription factor nuclear factor of activated T cells. However, Tsoutsman et al 6 did not find evidence of the activated upstream signaling mechanisms of the nuclear factor of activated T cells, mainly mitogen activated protein kinases, in tni-203/mhc-403 mice.…”
Section: Article P 1820mentioning
confidence: 99%